Sistem Keamanan Rumah Berbasis IoT Menggunakan Sensor PIR - Jayusman, Dwika; Armanto; Taqwa Martadinata, Ahamad (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2024)
The rapid development of technology has had a significant impact on various aspects of life, including in the field of home security. One of the innovations in home security systems is the application of Internet of Things (IoT) technology that utilizes PIR (Passive Infrared) sensors to detect human presence in the room. This research aims to design and implement an IoT-based home security system using Node MCU ESP8266 V.3 as a microcontroller and PIR sensor as a motion detector. Currently, theft often occurs in homes especially when the house is empty. This can cause hassle for homeowners. For this reason, it is necessary to have a system that allows users to monitor the condition of their homes. This system can be used in real-time via Websever on a smartphone device, which is connected to the internet network. With this system, it is expected that homeowners can quickly get notifications when there is suspicious activity in the house, especially when the house is empty. This research is also expected to contribute to the development of IoT-based security technology that is more effective and efficient. The results of this research show that the home security system built is able to function properly, provide real-time notifications, and improve overall home security. Based on the test results with several providers such as Indosat, 3 (Three) and Telkomsel, the results obtained are: if the distance between the sensor and the object ranges from 1 to 5 meters, the sensor will read and give a signal “There is Movement”, but if the sensor is rare from the object ranging from 6 to 10 meters, the sensor cannot read the movement.